Extending functional communication training to multiple language contexts in bilingual learners with challenging behavior. Issue 1 (27th September 2021) - Banerjee, Ipshita; Lambert, Joseph M.; Copeland, Bailey A.; Paranczak, Jessica L.; Bailey, Kathryn M.; Standish, Cassandra M.
Abstract : Little research has highlighted how evidence‐based practices (e.g., functional communication training [FCT]) might be adapted for bilingual learners with disabilities. In the current study, we served 2 children with autism spectrum disorder (ASD) and challenging behavior whose parents primarily spoke Spanish at home, and whose teachers primarily spoke English at school. Following traditional FCT (i.e., 1 language only), we systematically replicated the findings of Neely, Graber et al. (2020) by demonstrating that mands in the untrained language (i.e., English) did not emerge when trained mands (i.e., Spanish) contacted extinction in alternative‐language contexts. Simultaneously, challenging behavior consistently resurged. After children received explicit training with both languages and were taught to change the language of request when initial attempts were unsuccessful (i.e., "repair the message" training), these same children successfully obtained high rates of reinforcement in both language contexts, and challenging behavior rarely occurred.